PAEDIATRIC THROMBOSIS: A FIVE-YEAR EXPERIENCE FROM A TERTIARY CARE CENTER OF PAKISTAN - Rashid, Anila; Mansoori, Huma; Ali, Sidra Asad; Nasir, Nabeel (Journal of Ayub Medical College Abbottabad, 2022)
Background: Advances in imaging techniques and longer survival of chronic medical conditions contribute to the increase in paediatric thrombosis. We aim to determine the incidence, underlying risk factors, management and clinical outcome of paediatric thrombosis at a multidisciplinary facility of Pakistan. Methods: A retrospectively analysis of the medical records of patients in the paediatric age group admitted at the Aga Khan University hospital from January 2013-September 2018 was performed. Site of thrombosis, associated risks factors, management options and outcome of thrombotic event were evaluated. Results: Of the 22,320 paediatric hospitalization, 35 paediatric patients were diagnosed with thrombosis (15 cases per 10,000 admissions). The median age of the study group was 15 years and twenty patients (57%) were male. The commonest site of thrombosis was in lower limb venous 11 (31%), followed by upper limb venous thrombosis 6 (17%), abdominal vein thrombosis 7 (20%), cerebral venous thrombosis 5 (14%), pulmonary embolism and arterial thrombosis 3(9% each). Eighty three percent had underlying clinical condition including central venous catheter [CVC] (26%), malignancy and infection (14% each), antiphospholipid antibody syndrome (9%), inherited thrombophilia (9%), congenital heart disease (6%), while thrombotic thrombocytopenic purpura and autoimmune disorder (3% each). 12 (34%) patients were treated with heparin only, 8 (23%) received heparin followed by warfarin while warfarin as a single agent was given in 2 (5.7%) patients. One patient died of pulmonary embolism while 9(25%) had persistence or recurrence of thrombosis. Conclusion: Incidence of paediatric thrombosis was 0.15%. CVC placement was the most common associated risk factor. Warfarin and heparin both were found to be safe anticoagulation option. Recurrence rate was found to be high